Epidemiology of injury related disabilities in a selected district in Bangladesh: A cross-sectional study - Saidur Rahman Mashreky; AKM Fazlur Rahman; Mohammad Moniruzzaman; M Mostafa Zaman (Bangabandhu Sheikh Mujib Medical University Journal, 2023)
Globally more than a billion people are living with disabilities. Injuries are one of the major causes of disabilities. A cross-sectional survey was conducted in 2009 to explore the epidemiology of injury-related disability in a district of Bangladesh. A total of 37,039 populations were interviewed in 8905 households both in the urban and rural area. Overall prevalence of injury-related disability was found 6.8 per 1000 population. Significantly higher rate was observed in the rural area compared to urban. Compare to female the rate was found significantly higher among male (8.5; 95% confidence interval: 7.3-9.9), compared to female (5.0; 95% CI: 4.1-6.2). Rates were found to increase with age, the highest prevalence was found among 60 years and above age group where the rate was 24.3 (95% CI: 19.0-30.6) per 1000 population. Compare to literate people illiterate people were found more vulnerable (odds ratio 3.1; 95% CI 1.7-5.9). The prevalence among illiterate was 13.4 (95% CI: 11.1-16.1) per 1000 population, and it was 3.8 (95% CI: 2.0-6.5) among higher secondary & above education level population. Falls caused more than 32% disabilities. Road traffic injuries, cuts, machine injuries, burns, and violence were the other common causes of injury disability. About 30% of the people identified with an injury-related disability mentioned that they don’t use public transports, and 65% of them mentioned this is because of their disability. About 37% people reported that they had lost their job because of the disability. Injury share the significant cause of disability in Bangladesh. Fall, road traffic injury and cuts are the common causes of injury-related disabilities.